Adaptation of the Parents Taking Action program for Diné (Navajo) parents of children with autism - Lindly, Olivia J.; Running Bear, Candi L.; Henderson, Davis E.; Lopez, Kristina; Nozadi, Sara S.; Vining, Christine; Bia, Shannon; Hill, Erin; Leaf, Anna (Frontiers in Education, 2023)
Purpose: Neurodivergent children who are part of Indigenous communities in rural areas often have inequitable access to specialized services. Parent education and training programs can be used to help address these service system gaps. Yet few parent education and training programs exist for Indigenous parents of children with autism, including parents who identify as Diné (Navajo, meaning "The People"), the largest federated tribe in the United States. The Parents Taking Action (PTA) program is a parent education and training program delivered by community health workers that was originally developed for Latine parents of children with autism. The PTA program has been culturally adapted for other groups, and a growing evidence base exists supporting the program's feasibility, acceptability, and efficacy. We sought to adapt the PTA program for Diné parents. Method: This was a community-engaged case study on how the PTA program was adapted for Diné parents of children with autism. A community advisory board (CAB) of 13 individuals including Diné parents of children with autism and professionals helped guide the adaptation process. We interviewed 15 Diné parents of a child with autism about their needs and preferences for the PTA program and used this information to adapt the PTA program. CAB workgroups used the Ecological Validity Framework to provide input on adaptations to the original PTA program materials. We also obtained input on the program's adaptation from Diné communities and a PTA research collaborative. To incorporate the CAB's collective feedback on the PTA program adaptation, we modified terminology, visuals, and narratives. From the parent interview findings, we reduced the number of lessons and enabled community health workers to deliver lessons remotely. We further integrated Diné Parents Taking Action Program feedback from the CAB subgroups in the adaptation to specific lessons. We addressed feedback from the larger community by expanding our project's catchment area and involving additional programs.Conclusions: This case study demonstrates how an evidence-based, parent education and training program was adapted for Diné parents of children with autism. The adapted Diné PTA program is being piloted. We will improve Diné PTA by using the pilot's results and community input.